Multi-Stakeholder Synergy in Waste Management Toward a Clean and Sustainable North Sumatra - Nasution, Zaid Perdana; Tarigan, Vita Cita Emia; Affandi, Oding; Khair, Hafizhul; Sari, Yasmine Anggia; Bin Sanusi, Afriadi (Universitas Sumatera Utara, 2026)
Waste management in North Sumatra faces complex challenges encompassing technical, legal, institutional, and community behavior aspects. The increase in waste generation, unbalanced with adequate management capacity, impacts environmental quality and public health, thus requiring a sustainable, collaboration-based approach. This research analyzes the legal framework and policy implementation of waste management in North Sumatra through Stakeholder Analysis, exploring the roles, interests, and authorities of local governments, educational institutions, the private sector, and communities in the waste management system. This normative legal research with a limited empirical approach examines national and regional regulations, provincial and district/city policies, as well as field practices. The findings indicate that the legal substance provides an adequate normative basis, but policy effectiveness is hindered by weak institutional structures, limited infrastructure, and inconsistent law enforcement, which reduce public compliance and participation. Multi-stakeholder synergy serves as the key to enhancing effectiveness through policy innovations, institutional capacity building, and changes in community behavior. Strengthening the waste management model oriented toward source reduction, reuse, and environmentally friendly final disposal requires integration of legal substance, institutional structures, and community legal culture. The success of a clean and sustainable North Sumatra depends on consistent cross-sector collaboration within a framework of shared responsibility.